60-(3c+4)=4c+24+c

Simple and best practice solution for 60-(3c+4)=4c+24+c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60-(3c+4)=4c+24+c equation:


Simplifying
60 + -1(3c + 4) = 4c + 24 + c

Reorder the terms:
60 + -1(4 + 3c) = 4c + 24 + c
60 + (4 * -1 + 3c * -1) = 4c + 24 + c
60 + (-4 + -3c) = 4c + 24 + c

Combine like terms: 60 + -4 = 56
56 + -3c = 4c + 24 + c

Reorder the terms:
56 + -3c = 24 + 4c + c

Combine like terms: 4c + c = 5c
56 + -3c = 24 + 5c

Solving
56 + -3c = 24 + 5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5c' to each side of the equation.
56 + -3c + -5c = 24 + 5c + -5c

Combine like terms: -3c + -5c = -8c
56 + -8c = 24 + 5c + -5c

Combine like terms: 5c + -5c = 0
56 + -8c = 24 + 0
56 + -8c = 24

Add '-56' to each side of the equation.
56 + -56 + -8c = 24 + -56

Combine like terms: 56 + -56 = 0
0 + -8c = 24 + -56
-8c = 24 + -56

Combine like terms: 24 + -56 = -32
-8c = -32

Divide each side by '-8'.
c = 4

Simplifying
c = 4

See similar equations:

| 14-6x= | | -4.9x^2+7.4t+10.9=0 | | Lne^2=6 | | 4+5(3x-x)=4(8+2x) | | 2(-2n+5)=4-6n | | 7.36=-0.8(2x-1.2) | | 2(3+3x)=78 | | -9+6x=-3[3-2x] | | -13=m+3-8 | | 10x+20x=12x | | 4p+3=-13 | | -9=-9+x/7 | | (Z+4)and(z-6)=0 | | 5d-d-2d+8=0 | | 4y+8=2b | | 5(1-2n)-6n=37-8n | | (4w-3x)(2w+7x+5)= | | 3/4x+6=9-1/4x | | -2x+-2=4 | | 6cm+w=8cm | | d-18=8 | | 8x+10=-30 | | -3=n/10-4 | | -9v=3 | | -6=-2(h-9) | | 2(2a+2b)=10a-16b | | 4(2v+4)=-3-17 | | 4x+2(5x-1)+16=-28 | | 7x^2+53x+21=0 | | 7(y-2)=3y-34 | | 2(7x+7)=7(6x+6) | | p=4*s |

Equations solver categories